Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 170468 by MathsFan last updated on 24/May/22

 Given that log_4 (y−1)+log_4 ((x/y))=m   and log_2 (y+1)−log_2 x=m−1,   show that y^2 =1−8^m

$$\:\mathrm{G}{iven}\:{that}\:{log}_{\mathrm{4}} \left({y}−\mathrm{1}\right)+{log}_{\mathrm{4}} \left(\frac{{x}}{{y}}\right)={m} \\ $$$$\:{and}\:{log}_{\mathrm{2}} \left({y}+\mathrm{1}\right)−{log}_{\mathrm{2}} {x}={m}−\mathrm{1}, \\ $$$$\:{show}\:{that}\:{y}^{\mathrm{2}} =\mathrm{1}−\mathrm{8}^{{m}} \\ $$

Answered by cortano1 last updated on 24/May/22

   { ((log _4 (y−1)+log _4 ((x/y))=m)),((log _2 (y+1)−log _2 x=m−1)) :}    { ((log _2 (((y−1)/y))+log _2 x = 2m)),((log _2 (y+1)−log _2 x=m−1)) :}  (1)+(2)  ⇒log _2 (((y^2 −1)/y))=3m−1  ⇒((y^2 −1)/y) = (8^m /2)

$$\:\:\begin{cases}{\mathrm{log}\:_{\mathrm{4}} \left({y}−\mathrm{1}\right)+\mathrm{log}\:_{\mathrm{4}} \left(\frac{{x}}{{y}}\right)={m}}\\{\mathrm{log}\:_{\mathrm{2}} \left({y}+\mathrm{1}\right)−\mathrm{log}\:_{\mathrm{2}} {x}={m}−\mathrm{1}}\end{cases} \\ $$$$\:\begin{cases}{\mathrm{log}\:_{\mathrm{2}} \left(\frac{{y}−\mathrm{1}}{{y}}\right)+\mathrm{log}\:_{\mathrm{2}} {x}\:=\:\mathrm{2}{m}}\\{\mathrm{log}\:_{\mathrm{2}} \left({y}+\mathrm{1}\right)−\mathrm{log}\:_{\mathrm{2}} {x}={m}−\mathrm{1}}\end{cases} \\ $$$$\left(\mathrm{1}\right)+\left(\mathrm{2}\right) \\ $$$$\Rightarrow\mathrm{log}\:_{\mathrm{2}} \left(\frac{{y}^{\mathrm{2}} −\mathrm{1}}{{y}}\right)=\mathrm{3}{m}−\mathrm{1} \\ $$$$\Rightarrow\frac{{y}^{\mathrm{2}} −\mathrm{1}}{{y}}\:=\:\frac{\mathrm{8}^{{m}} }{\mathrm{2}} \\ $$$$ \\ $$

Commented by MathsFan last updated on 24/May/22

thanks

$${thanks} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com